Prenatal Somatic Cell Gene Therapies: Charting a Path Toward Clinical Applications (Proceedings of the CERSI‐FDA Meeting). (15th September 2022) - Herzeg, Akos; Almeida‐Porada, Graça; Charo, R. Alta; David, Anna L.; Gonzalez‐Velez, Juan; Gupta, Nalin; Lapteva, Larissa; Lianoglou, Billie; Peranteau, William; Porada, Christopher; Sanders, Stephan J.; Sparks, Teresa N.; et al.
Abstract: We are living in a golden age of medicine in which the availability of prenatal diagnosis, fetal therapy, and gene therapy/editing make it theoretically possible to repair almost any defect in the genetic code. Furthermore, the ability to diagnose genetic disorders before birth and the presence of established surgical techniques enable these therapies to be delivered safely to the fetus. Prenatal therapies are generally used in the second or early third trimester for severe, life‐threatening disorders for which there is a clear rationale for intervening before birth. While there has been promising work for prenatal gene therapy in preclinical models, the path to a clinical prenatal gene therapy approach is complex. We recently held a conference with the University of California, San Francisco–Stanford Center of Excellence in Regulatory Science and Innovation, researchers, patient advocates, regulatory (members of the Food and Drug Administration), and other stakeholders to review the scientific background and rationale for prenatal somatic cell gene therapy for severe monogenic diseases and initiate a dialogue toward a safe regulatory path for phase 1 clinical trials. This review represents a summary of the considerations and discussions from these conversations.